TINDAKAN PROMOSI SAHAM OLEH FIGUR PUBLIK DI MEDIA SOSIAL - Rizki (2022)
The rapid development of the number of investors in Indonesia does not go hand in hand with the development of public knowledge related to the capital market. Due to the lack of public knowledge in this field, it becomes a gap for crime to obtain unilateral profits, one of which is using the stock pom-pom scheme through stock promotion actions carried out by public figures on social media.. Through normative legal research using a conceptual approach and a statutory approach, by looking at the phenomena that are happening in the community, it can be seen indications of violations of capital market laws in stock promotion actions by public figures. The existence of public figures with their promotional actions, has a positive impact as well as a negative impact on activities in the capital market. The public as investors are expected to be more careful in making decisions when operating in the capital market. OJK as a supervisory and regulatory agency in the capital market plays an important role in dealing with crimes that occur in the capital market. It is hoped that law enforcement officers in Indonesia will not ease the supervision and prosecution of criminal practices in the capital market which should be resolved through criminal trials in court.